Alterações renais causadas pela lectina de sementes de Vatairea Macrocarpa - Monteiro, Ana Maria de Oliveira (2004)
Lectins are glycoproteins that interact reversibly and specifically with carbohydrates. The Vatairea macrocapa lectin (VML) is a galactose-binding lectin present in the family leguminosae and in the tribe Dalbergieae. ln the present study, we investigated the effect of Vatairea macrocarpa lectin (VML) in the isolated rat kidneys, as well as histological changes. Isolated kidneys from Wistar rats, weighing 240 to 280g, were perfused with Krebs-Henseleit solution containing 6% of bovine serum albumin. The parameters studied included perfusion pressure (PP), renal vascular resistance (RVR), glomerular filtration rate (GPR), urinary flow (UF), percent of sodium tubular transport (%TNa+), percent of potassium tubular transport (%TK+) and percent of chloride tubular transport (%TCl-). The latairea macrocarpa lectin (10 µg/mL) increased the PP, RVR, UF and GPR. On the other hand, VML did not change the %TNa+, %TK+ and % TCl-. The lectin plus galactose complex (Gal-VML) signihcantly blocked the increase in the PP, RVR, UF and RFG. ln the control group showed a small amount of a proteinaceous material in the urinary space, although no alteration in the renal tubules was detected. The administrated of galactose alone did not modify the functional kidney parameters. The kidneys perfused with /ML showed moderate deposit of proteinaceous material in the tubules and urinary space. ln the kidneys pretreated with Gal-VML had only small amount of a proteinaceous material in the urinary space. But no abnormalities were seen in renal tubules. These results suggest that lectin from Vatairea macrocarpa seeds presents important effect on renal system reported carbohydrate-binding site, taken into account that showed the reversion of renal effects using the inhibitor specific. The current experiments are first demonstration of biological action of VML in the isolated kidney.